Efektivitas BlendedLearningdan Diskusi-Presentasi terhadap Hasil Belajar ditinjau dari Kemampuan Verbal-LingusticMahasiswa STIT Muhammadiyah Tempurrejo Ngawi Tahun Ajaran 2016/2017 - ansori, miksan (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Blended Learning is a new method and deemed in accordance with the current ICT developments. In addition to the needfor study on the method, blended learning is also feltable to answer the problem of the lack of learning in university that still rely discussion-presentation teaching. This study has the aim to determi new het hert here sult sof student learning with blended learning method is better than the method of discussion-presentation viewed from verbal-linguistic ability. This study uses a quantitative approach to the type of quasi-experimental, by trying out of a treatment. Techniques hypothesis testing using analysis of variance (ANOVA) two way swith a 2 x 2 factorial (Î± = 5%) and the prerequis itetestu sedis thea veragesimilarity test, test of normality and homogenity test. The result so btained are (1) the result sof student learning with blended learning method is better than the result sof student learning with the method of discussion-presentation. (2) There is significant influence levels of verbal-linguistic to ward student learning out comesand (3) the result sof student learning with blended learning method is better than the the result sof student learning with the method of discussion-presentation, bothfor students with higho rlow verbal-linguistic abilities.